Peningkatan Kemandirian Energi dan Pangan Berbasis Teknologi Digester Biogas Tipe Fixed Dome di Pedesaan: Pengabdian - Ashar Pramono; Siti Ruqaiyah Baharuddin; Andi Muhammad Akram Mukhlis; Andi Muhammad Taufik Ali; Syakia Muflihat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community empowerment program aims to optimize livestock waste as a source of renewable energy and organic fertilizer at the Bontomarannu Livestock Farmers Group in Batang Village, Bulukumba Regency. The main problems include poor sanitation of cages, unmanaged livestock waste, and high household dependence on expensive and scarce LPG. Activities are carried out through a participatory approach which includes socialization, training, technical assistance, construction of a fixed-dome type biogas installation with a capacity of 4 m³, and the construction of environmentally friendly livestock pens. All infrastructure has been successfully completed and operates optimally. The digester produces 2.5–3.5 hours of gas per day so that it can reduce LPG consumption by 2 cylinders per month. By-products in the form of bioslurry are used to become solid and liquid organic fertilizers, with an initial production of 40-60 kg/month. This program has a positive impact on energy security, improving environmental quality, and agricultural productivity, while